Corpus Callosum Radiomics-Based Classification Model in Alzheimer's Disease: A Case-Control Study - Feng, Qi; Chen, Yuanjun; Liao, Zhengluan; Jiang, Hongyang; Mao, Dewang; Wang, Mei; Yu, Enyan; Ding, Zhongxiang (Frontiers in Neurology, 2018)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disease causes the decline of some cognitive impairments. The present study aimed to identify the corpus callosum (CC) radiomic features related to the diagnosis of AD and build and evaluate a classification model. Methods: Radiomics analysis was applied to the three-dimensional T1-weighted magnetization-prepared rapid gradient echo (MPRAGE) images of 78 patients with AD and 44 healthy controls (HC). The CC, in each subject, was segmented manually and 385 features obtained after calculation. Then, the feature selection were carried out. The logistic regression model was constructed and evaluated according to identified features. Thus, the model can be used for distinguishing the AD from HC subjects. Results: Eleven features were selected from the three-dimensional T1-weighted MPRAGE images using the LASSO model, following which, the logistic regression model was constructed. The area under the receiver operating characteristic curve values (AUC), sensitivity, specificity, accuracy, precision, and positive and negative predictive values were 0.720, 0.792, 0.500, 0.684, 0.731, 0.731, and 0.583, respectively. Conclusion: The results demonstrated the potential of CC texture features as a biomarker for the diagnosis of AD. This is the first study showing that the radiomics model was a valuable method for the diagnosis of AD.